Characterizations of Nnce-open and Nnce-closed Functions (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this paper is to introduce and investigate several new classes of functions called, Nnce-open and Nnce-closed functions in Nnc topological spaces by using the concept of Nnce-open sets. Several new characterizations and fundamental properties concerning of these new types of functions are obtained. Furthermore, these kinds of functions have strong application in the area of image processing and have very important applications in quantum particle physics, high energy physics and superstring theory